Baptist ethics of conscientious objection to military service in South Africa: the watershed case of Richard Steele - F. Hale (Acta Theologica)
Although the Baptist Union of Southern Africa included relatively few outspoken critics of the apartheid system, during the 1970s and 1980s a small number of its younger members confronted the military system which supported that system of social engineering by refusing to comply with military conscription. Particularly noteworthy among these dissenters was Richard Steele, who had been influenced by the Anabaptist tradition of pacifism in the United States of America. Like his cousin and fellow Baptist, Peter Moll, he countered prevailing sentiments and practices within his denomination by going to prison rather than serve in the South African Defence Force. Steele’s action met with little support in the Baptist Union.